FUTURE SOCIAL MEDIA USE WITH THE EMERGENCE OF AI IN MALAYSIA AND INDONESIA - Mohamed Tahir , Muhammad Zainul Abidin; Othman, Roslina (Malaysian Journal of Computer Science, 2025)
This study explored the future uses of social media in Malaysia and Indonesia. There were 28.68 million social media users in Malaysia and 167 million in Indonesia. Most of the 10,211 users in the United States said that social media had a largely negative impact. Another survey found that 39% of the users in the United States posited that by 2035, uses of social media would not significantly serve the public good, and 18% said social media was evolving to a worse future for society. The objectives were to explore the potential, emerging trends, and future social media uses in Malaysia and Indonesia through content analysis, the Delphi survey, and triangulation. The content analysis analyzed 40 websites using QDA Miner and WordStat 9 for theme and case identification. The Delphi survey was constructed from existing studies and distributed to 12 experts. The findings revealed that potential social media uses comprised artificial intelligence-enhanced social commerce, socio-political attempts, and the need for control mechanisms enforced by the authorities. The emerging trends included the creation of non-traditional families and social chatbots. The preferable futures of social media use comprised augmented and virtual reality, audience analytics, conversational commerce, AI-powered chatbots, digital citizenship, and virtual campaigns against online scammers. The values of social media use included narrative control, compliance with Maqasid al-Shariah, regulated technological designs, and safety in the virtual environment. The study recommended an expanded ethical guideline for social media use and an action plan for regulating social media use in the future.